Coaching and Mentoring for Edupreneurs in the Era of Marketing Phygital 6.0 - Lili Adi Wibowo; Tika Koeswandi; Lisnawati Lisnawati (Journal of Community Service and Empowerment, 2025)
Marketing training based on phygital 6.0 marketing for students in the ambassador of business edupreneur is a marketing 6.0 training model (phygital) is designed to provide an in-depth understanding of the world of digital business and entrepreneurial marketing for students in the Faculty of Education and Business. Phygital Marketing combines elements of physical marketing (offline) and digital marketing (online) to create a holistic experience for consumers. The participants involved were 50 students from the Faculty of Economics and Business Education (FPEB) at the Indonesian Education University who took part in The Ambassador of Business Edupreneur activities. The CLEAR model was chosen because it offers a flexible and adaptable framework for coaching sessions, making it suitable for a variety of contexts, including personal, professional, and business development. The program brought about significant improvements in how educational entrepreneurs approach marketing and business development in a digitally integrated world. One of the key improvements was the participants' enhanced understanding of Phygital 6.0 concepts. Edupreneurs gained a deeper comprehension of how to effectively blend physical and digital marketing strategies to create a seamless customer experience. This understanding allowed them to rethink their marketing approaches, focusing on integrating emerging technologies like augmented reality (AR), virtual reality (VR), and artificial intelligence (AI) through social media and e-commerce platforms into their educational business offerings. By doing so, they could offer more engaging, personalized, and interactive experiences for their learners, which in turn increased the value and reach of their products and services.